Plots and plantations - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
A forest superintendent from Nigeria explains how policy needs to change in order to reduce the amount of natural forest that is lost to cash crop plantations and agriculture.